SOLUTIONS OF THE DIOPHANTINE EQUATION 15^x+4^y=z^2 - Kambheera, Abhiwat; Kumpapan, Kiattisak (Life Sciences and Environment Journal, 2020)
In this paper, we study solutions of the Diophantine equation 15x+4y=z2 has a unique non-negative integers. We found that this equation has solution exactly (x, y,z) = (1, 0, 4)